Comparison of real-world emissions of LDGVs of different vehicle emission standards on both mountainous and level roads in China. (April 2019) - Zhang, Lanyi; Hu, Xisheng; Qiu, Rongzu; Lin, Jane
Highlights: To characterize vehicle emissions in a mountainous terrain in China using PEMS. To examine the gaseous emissions of LDGVs of different Chinese emission standards. To investigate the effects of mountainous terrain on VSP and emissions. Current emission standards on unburned hydrocarbons are stagnant in China. Current operating mode classification in MOVES is not adequate for mountainous roads. Abstract: Light-duty gasoline vehicles (LDGVs) account for the largest portion of all in-use vehicles and a substantial amount of emissions in China. Among many contributing factors, the joint effect of driving conditions and road grade in a mountainous terrain on vehicle emissions is much less studied than on a level terrain, especially in China. This study presents a real-world investigation of gaseous pollutants (CO, NOx, and HC) and greenhouse gas (CO2 ) emissions from LDGVs of different Chinese emission standards ranging from China 3 to China 5. Two driving routes representative of the characteristics of a mountainous and a level road respectively were selected, and instantaneous emissions and other relevant data were collected with the Portable Emission Measurement Systems (PEMS). The results demonstrate the statistically significant impact of road grade on the vehicle specific power (VSP) and emissions even after controlling for speed and acceleration (drive schedule) and emission control standards. An analysis of variance (ANOVA) reveals that, within each of the MOVES-defined operating modes, statistically different emissions are observed across different road grade levels. In other words, the current MOVES-defined operating modes may be inadequate for binning and modeling vehicle emissions of a mountainous terrain. When establishing an emission model for China, more careful classification of operating modes is needed by road grade and terrain type. The study also reveals the lack of improvement in the real-world HC emission control as a result of the stagnant HC emission standards particularly between China 4 and China 5.